PENERAPAN METODE YANBU’A DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA DI MI NURUL MUN’IM - Khusnul Laili; Zakiyah Bz (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The ability to read the Qur’an fluently and accurately in accordance with the rules of tajwid is a fundamental competency that must be possessed by students of Madrasah Ibtidaiyah (MI) Nurul Mun’im. However, the reality of learning shows that many students still experience difficulties in reading fluency, accuracy of makhraj, and the application of tajwid. This study aims to analyze the implementation of the Yanbu’a method and its impact on students’ Qur’an reading ability at MI Nurul Mun’im. The study employs a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation involving Qur’an teachers, the head of the madrasah, the vice principal for curriculum affairs, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing using triangulation techniques. The findings indicate that the Yanbu’a method is implemented through learning planning based on students’ initial abilities, consistent instructional practices involving direct reading and immediate correction, as well as tiered and continuous evaluation. The implementation of this method has been shown to improve students’ Qur’an reading ability, particularly in terms of reading fluency, accuracy of makhraj, application of tajwid rules, and students’ confidence in reading the Qur’an.